Bond mutual funds vs. bond exchange traded funds: Evaluation of risk adjusted performance - Jelena Stankevičienė; Ieva Petronienė (Administrative Sciences, 2019)
Growing acceptance of passive bond exchange traded funds (ETFs) and actively managed bond mutual funds has exposed the need to find a divide between these two comparatively similar types of instrument. This paper provides a comparative analysis of actively managed bond funds and passive bond ETFs in the context of multiple criteria. The research of risk-adjusted performance of a sampled group of bond funds and ETFs using the TOPSIS multi-criteria decision-making method revealed that actively managed bond funds have a modest advantage over passive bond ETFs. Moreover, the final findings indicate the funds' performance dependability on portfolio composition by fixed income sector.
Keywords: 350; exchange traded funds (ETF); risk; performance; bonds; TOPSIS